Bacteriological Profile Of Ear Discharge And Their Antibiotic Sensitivity In Chronic Suppurative Otitis Media In Kashmir,India - Yousuf, A; Malik, M; Shamas, IU; Beigh, Z; Kumari, S; Pampori, PRA (Bangladesh Journal of Medical Science, 2012)
The objective of the study was to study the microflora and the antibiograms of patients with chronic suppurative otitis media (CSOM) in Kashmir,in order to provide a guidelines for making a protocol for empirical antibiotic therapy. Study design:Prospective study Material and methods: This study was conducted on OPD basis in Department of Ear, Nose and Throat and HNS Government medical college Srinagar kashmir from july 2010 to june 1011 and one hundred twenty five(125) patients with unilateral or bilateral active chronic suppurative otitis media were prospectively studied.They had chronic ear discharge and had not received antibiotics for the previous five days. Swabs were taken from discharging ear's and sent to microbiological section of hospital were culture for bacteria was done Antibiotic sensitivity testing was done with standard antibiotic discs using Kirby-bauer disk diffusion method.4 Results:From the Clinical specimens off the 125 patients microbiological culture was positive in 110 specimens. The most common causal organisms isolated were Staphylococcus aureus (48%) including 8% of methcillin resistant staph aureus and Pseudomonas aeruginosa (16%) followed by coagulase negative.Antibiotic sensitivities of staph aureus (other than MRSA) showed that 72% isolates were sensitivity to gentamicin,55% to ciprofloxacin followed by 36% to cephalosporins (cetazidime,ceftriaxone) .For pseudomonas aeruginosa 72% isolates were sensitive to piperacillin/tazobactum 48% to ciprofloxacin and 32% to ceftazidime/ceftriaxone. Of the three antibiotics commonly available as topical eardrops,ciprofloxacin and gentamicin has the highest susceptibility rate. DOI: http://dx.doi.org/10.3329/bjms.v11i3.11731 Bangladesh Journal of Medical Science Vol. 11 No. 03 July12